2011
DOI: 10.1097/brs.0b013e3181ef610b
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Spinal Cord Expression of Fractalkine and its Receptor in a Rat Model of Disc Herniation by Autologous Nucleus Pulposus

Abstract: Our results indicate that autologous implantation of NP induces thermal hyperalgesia and mechanical allodynia, and leads to an upregulation of fractalkine and its receptor in spinal neurons and glia, implicating fractalkine in association with radicular pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 51 publications
1
23
0
1
Order By: Relevance
“…Recently, we reported that autologous implantation of NP on a nerve root in a rat caused upregulation of fractalkine in the spinal dorsal horn, which suggests that fractalkine is associated with radicular pain. 33 Our results are consistent with the notion that inflammatory responses, rather than mechanical compression, caused by NP are responsible for pain and suggest that some cellular changes occur after PRF administration to the DRG in a rat model of lumbar disc herniation.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Recently, we reported that autologous implantation of NP on a nerve root in a rat caused upregulation of fractalkine in the spinal dorsal horn, which suggests that fractalkine is associated with radicular pain. 33 Our results are consistent with the notion that inflammatory responses, rather than mechanical compression, caused by NP are responsible for pain and suggest that some cellular changes occur after PRF administration to the DRG in a rat model of lumbar disc herniation.…”
Section: Discussionsupporting
confidence: 81%
“…Transplantation of autologous NP near a spinal nerve root is frequently used in animal models of lumbar intervertebral disc herniation, 17,19,29,31,33,34,41 and NP application without compression of the nerve root and DRG produces morphologic and functional changes and blood flow impairment, 18,30,51 enhances responses of secondary neurons to noxious stimuli, 3 and causes allodynia in the hindlimb. Recently, we reported that autologous implantation of NP on a nerve root in a rat caused upregulation of fractalkine in the spinal dorsal horn, which suggests that fractalkine is associated with radicular pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al19 found that CX3CL1 immunoreactivity gradually increased in laminae II and III of the ipsilateral dorsal horn by using a nucleus pulposus (NP) implantation-induced model of LDH. One recent study showed that CCL2/CCR2 signaling in the dorsal root ganglion and spinal cord plays a significant role in the maintenance of neuropathic pain in a rat model of LDH 20…”
Section: Introductionmentioning
confidence: 99%
“…For instance, previous data show that soluble fractalkine (CX3CL1) activates glia and leukocytes through its receptor CX3CR1 [11, 12]. Furthermore, spinal upregulation of CX3CL1 may be associated with mechanical allodynia and thermal hyperalgesia [13]. Thus, one important inflammatory molecule possibly influencing the sensory pathways may be CX3CL1.…”
Section: Introductionmentioning
confidence: 99%